1976
DOI: 10.1128/aac.9.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Beta-Hemolytic Streptococci to 65 Antibacterial Agents

Abstract: Tests for susceptibility of 29 group A, 4 group C, and 2 group G strains of beta-hemolytic streptococci to 63 antibiotics and to trimethoprim and sulfamethoxazole, singly and combined in a ratio of 1:16, were carried out in vitro. All strains tested were moderately or highly susceptible to all the antibiotics used except those belonging to the aminoglycoside and polymyxin groups. A few were also resistant to the tetracyclines and to sulfamethoxazole alone. Comparisons with results obtained in previous years in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…9 However, despite the past two decades of research on penicillin-resistant strains, all the obtained isolates have shown susceptibility to penicillin at an MIC of 0.06 µg/ml. 10,11 This means that, although penicillin has been used for six decades or so in clinical practice, bacterial in-vitro susceptibility to this agent has not changed noticeably. All the isolates we tested in this report also showed susceptibility to penicillin.…”
Section: Discussionmentioning
confidence: 97%
“…9 However, despite the past two decades of research on penicillin-resistant strains, all the obtained isolates have shown susceptibility to penicillin at an MIC of 0.06 µg/ml. 10,11 This means that, although penicillin has been used for six decades or so in clinical practice, bacterial in-vitro susceptibility to this agent has not changed noticeably. All the isolates we tested in this report also showed susceptibility to penicillin.…”
Section: Discussionmentioning
confidence: 97%
“…All of the studies reporting high resistance rates either used media known to have high concentrations of thymidine or did not provide details of the medium used. As standardization to ensure a low thymidine concentration of Mueller-Hinton medium was introduced only in 2006, it is likely that, unless low-thymidine media were specified (2,14,18,22,26,44,54), studies in publications prior to this may not have controlled for thymidine content.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reported clinical failures in the use of this agent in eradicating S. pyogenes from nasopharyngeal carriage (30). However, other centers have demonstrated full in vitro susceptibility of S. pyogenes to SXT (14,22,36,54). Since 2006, when the thymidine content of MHA became strictly regulated by the Clinical and Laboratory Standards Institute (CLSI) to maintain a low level of thymidine and hence avoid inhibition (M6-A2 protocol) (9), it has no longer been necessary to add lysed horse blood to the medium for AST.…”
mentioning
confidence: 99%
“…In one survey from 1965 at the Karolinska Hospital in Stockholm, Sweden, a resistance frequency of about 20% was found. Later, a similar study at the Boston City Hospital in 1972 showed 8.6% resistance (8).…”
mentioning
confidence: 89%